Sampling moiré as a special windowed Fourier ridges algorithm in demodulation of carrier fringe patterns - Kemao, Qian (2019)
In recent times, both the windowed Fourier ridges (WFR) and sampling moiré (SM) algorithms have been extensively used due to their high effectiveness in the demodulation of carrier fringe patterns. As they are developed independently, they are mostly recognized as completely different techniques, but we theoretically prove that SM is a special WFR with a specific window shape and a preset local frequency. This unifies the two different algorithms and enhances the understanding of their theoretical aspects, which helps to simplify the selection of these algorithms in real applications.